Relationship Between Intensive Care Nurses' Attitudes and Behaviors Toward End-of-Life Care and Ethical Attitudes - Efil, Sevda; TÜREN, SEVDA; Demir, Gül (Lippincott Williams & Wilkins, 2023)
Background: Nurses are in a central position to improve care for dying patients and their families by challenging current end-of-life practices in their settings. Nurses who care for such patients experience the associated ethical dilemmas. However, the relation between their attitude and behavior regarding end-of-life care and their ethical attitudes is not known. Objectives: The aim of this study was to examine the relation between the attitudes and behaviors of intensive care unit nurses to end-of-life care and their ethical attitudes in the care process. Methods: The research was conducted in Antalya, one of the most populous provinces in Turkey, with 287 intensive care nurses working in 4 different hospitals. The research data were collected between June 30 and August 30, 2021. Self-report data were collected using a Nurses' Description Form, the Attitudes and Behaviors of ICU Nurses to End-of-Life Care Scale, and the Ethical Attitude Scale for Nursing Care. Results: The mean score of the intensive care nurses for attitude and behaviors to end-of-life care was 62.36 ± 13.22, and their mean score for ethical attitude for nursing care was 149.76 ± 24.98. Conclusion: It was found that intensive care nurses' attitudes and behaviors to end-of-life care had a positive correlation on their ethical attitudes in the care process (P < .001). Discussion: It would be of interest to understand how these attitudes impact clinical decision-making for the ultimate understanding of whether nurses' attitudes can be a barrier to the delivery of quality end-of-life care.
Keywords: Attitude; Behavior; End-of-life Care; Ethics of Care/Care Ethics; Nurse